The Problems of The Population in Indonesia - Nissa Maudi Yasmin (IRDH International Journal of Social Sciences & Humanities, 2025)
Indonesia is a country that has the 4th largest population in the world after China, India and the United States. Population growth is accelerating, encouraging the development of aspects of life which include social, economic, political, cultural and so on. this article aims to uncover population problems in Indonesia in the current era, as a reference basis for determining population policies in the future. This study uses a literature review method. The Population problems in Indonesia consist of two aspect, there are demographic issue and non-demographic issue. The demographic issue are Large Population, High Population Growth Rate, and Uneven Distribution of Population. Otherwise, the non-demographic issue are Stunting of Children, Human Development Index, and also Poverty. Population policy is a policy aimed at influencing the size, composition, distribution and level of population development. Thus, it is hoped that a good balance will be achieved between the number and speed of population growth and the development of production and services